Research on the related between microstructures and impact toughness of Ti80 alloy - Bin Hu; Jinyang Ge; Junyang He; Bin Kong; Xiaoyong Zhang; Kechao Zhou (Journal of Materials Research and Technology)
Ti80 alloy with different microstructures, i.e., fully equiaxed αp (FE), equiaxed αp + colony-distributed thick lamellae αl (ECL), and equiaxed αp + disorder-distributed thin lamellae αl (EDL) were tailored to unravel the correlation between microstructure and impact toughness. In particular, the FE and ECL exhibited superior impact toughness (132.5 J/cm2 and 110.0 J/cm2 respectively), nearly twice that of EDL (65.0 J/cm2). By investigating the microstructure deformation mechanisms and crack deflection behaviors, we found that equiaxed αp and colony αl in FE or ECL possess superior abilities of plastic deformation and crack deflection, promoting severe deformation of them, tortuous crack paths as well as high energy dissipation. However, EDL exhibited a straight crack path caused by low resistance to crack propagation of disorder-distributed thin αl. Furthermore, the activation of high-density {10 1‾ 2}<10 1‾ 1> twins in FE and ECL, effectively released the local stress concentration, facilitated dislocation slip, and refined matrix grains, improving the deformation compatibility. Note that the interstitial β-phase in the αl colony in ECL offered new α/β interfaces and prevented dislocation mobility to a certain extent. This, on one hand, slightly lower the impact toughness as compared to FE, and on the other hand, greatly enhanced the overall strength level. Consequently, ECL demonstrated the best combination of strength and toughness.